Coastal Fishers Livelihood Behaviors and Their Psychosocial Explanations: Implications for Fisheries Governance in a Changing World - Evan J. Andrews; Evan J. Andrews; Sarah Wolfe; Prateep K. Nayak; Derek Armitage (Frontiers in Marine Science, 2021)
This research is a critical examination of the behavioral foundations of livelihood pathways over a 50-year time period in a multispecies fishery in Newfoundland and Labrador, Canada. Fishers make difficult decisions to pursue, enjoy, and protect their livelihoods in times of change and uncertainty, and the resultant behaviors shape efforts to advance sustainability through coastal and marine fisheries governance. However, there is limited evidence about fishers’ behavioral changes over long time periods, and the psychosocial experiences that underpin them, beyond what is assumed using neoclassical economic and rational choice framings. Our analysis draws on 26 narrative interviews with fishers who have pursued two or more fish species currently or formerly. Fishers were asked about their behavioral responses to change and uncertainty in coastal fisheries across their entire lifetimes. Their narratives highlighted emotional, perceptual, and values-oriented factors that shaped how fishers coped and adapted to change and uncertainty. The contributions to theory and practice are two-fold. First, findings included variation in patterns of fisher behaviors. Those patterns reflected fishers prioritizing and trading-off material or relational well-being. With policy relevance, prioritizations and trade-offs of forms of well-being led to unexpected outcomes for shifting capacity and capitalization for fishers and in fisheries more broadly. Second, findings identified the influence of emotions as forms of subjective well-being. Further, emotions and perceptions functioned as explanatory factors that shaped well-being priorities and trade-offs, and ultimately, behavioral change. Research findings emphasize the need for scientists, policy-makers, and managers to incorporate psychosocial evidence along with social science about fisher behavior into their models, policy processes, and management approaches. Doing so is likely to support efforts to anticipate impacts from behavioral change on capacity and capitalization in fleets and fisheries, and ultimately, lead to improved governance outcomes.